포제션 개념을 적용한 한국남자프로농구 승률 예측 분석 - 류지호; Jiho Ryu; 한진욱; Jin-wook Han; 김민수; Minsoo Kim (Ch'eyuk kwahak yŏn'gu, 2018)
[목적] 본 연구는 기존의 농구 기록 관련 연구에서 다뤄지지 않았던 포제션의 개념을 적용하여 한국남자프로농구의 승률을 예측하는데 목적이 있다. [방법] 한국남자프로농구 1997-1998시즌부터 2016-2017시즌의 자료를 대상으로 선정하여 분석했다. 1차 자료 수집으로 얻은 각 팀의 기록에 NBA에서 사용하는 포제션 산출 공식을 적용하여 팀별 포제션당 팀 평균기록을 산출하였다. 이러한 데이터를 바탕으로 상관분석, 다중회귀분석, Fisher의 Z 변환 및 단계적 다중회귀분석을 실시했으며 다음과 같은 결과를 도출하였다. [결과] 첫째, 포제션당 팀 평균기록은 경기당 팀 평균기록보다 팀 승률에 대한 설명력이 더 큰 것으로 나타났다. 둘째, 포제션당 팀 평균기록으로 팀 승률을 예측했을 때, 수비 리바운드, 2점슛 성공률, 스틸, 3점슛 성공률, 자유투시도, 턴오버, 공격 리바운드, 블록슛, 자유투 성공률, 어시스트 순으로 영향을 미치는 것으로 나타났다. [결론] 이러한 연구를 고려해볼 때 농구 경기의 데이터 분석 연구에서 포제션을 토대로 하는 후속연구가 활발히 이루어고, 다양한 관점에서 농구 경기 데이터를 분석하고 해석하는 시도가 진행될 것으로 기대된다. [Purpose] The purpose of this study was to predict winning percentage in the Korean Basketball League(KBL) by applying the possession concept. [Method] The model to estimate possession was utilized by formula used in NBA(National Basketball Association). Data consist of 20 seasons of the KBL (1997-2017). For data analysis, multiple regression analysis, Fisher’s Z transformation and stepwise multiple regression analysis were performed using SPSS 22.0. [Results] The result indicated that average team stats per possession had more explanatory power in predicting the KBL teams’ winning percentage than average team stats per game. The most important factor for winning in the KBL was defensive rebounds and followed by 2-point field goal percentage, steals, 3-point field goal percentage, free throw attempts, turnovers, offensive rebounds, blocked shots, free throw percentage, and assists. The results of this study provided fundamental information for the data analysis of Korean basketball games. It might be useful for basketball coaches to manage and instruct their teams. [Conclusions] Practical implications and future research direction were also suggested.